FITS Format for Planetary Surfaces: Definitions, Applications, and Best Practices. Issue 10 (13th October 2018) - Marmo, C.; Hare, T. M.; Erard, S.; Minin, M.; Pineau, F.‐X.; Zinzi, A.; Cecconi, B.; Rossi, A. P.
Abstract : Planetary science encompasses a broad number of research fields and brings together several research communities (geologists, astronomers, physicists, geochemists, etc.). Planetary missions produce an impressively growing amount of diverse data requiring an evolution from a mostly manual‐based visual analysis to a more automated and quantitative analysis. Interoperability, openness of data formats, and shared processing techniques are a necessity to efficiently extract scientific information from the data and to guarantee the reproducibility of the scientific results. Unfortunately, the technologies and data formats used by researchers for planetary surface studies and the field of astronomy diverged as these related, but almost completely isolated, domains evolved. In this paper we will describe how a small addition to the Flexible Image Transport System (FITS) standard, widely used in the astronomy investigations, will allow FITS to be more easily used in planetary surface investigations. We will also show how FITS metadata can easily be transformed in the Planetary Data System version 4 metadata archival model and lastly provide example implementations. More than imposing a formal data model, a FITS description for planetary data aims to simplify sharing data across the planetary and astronomy domains and promoting interoperability from raw data formatting to final visualization. Key Points: We present an extension of FITS metadata for planetary surface investigations A FITS description for planetary data aims to simplify sharing data across the astronomy and planetary domains An open FITS portrayal will promote interoperability from raw data formatting to final visualization